Sheet chair technology from pine wood species / Mohamad Hazlin Nurul Huda - Nurul Huda, Mohamad Hazlin (Faculty of Applied Sciences, 2019)
Nowadays, the consumer house space is limited an difficult for them to arrange properly. The space of house recently becomes limited and there will be addition of furniture that can narrow the spaces inside the house. The production of sheet Chair Technolgy from the pine Wood for space saving' design was conducted. Pine wood is fast growing tree and there will always some leftover after the tree being processed into a timber. This project focused on wastage from the Pine wood that can be used to produce a value adde product. Customers satisfaction survey of the product was evaluated based on the questionnaire. The questionnaire was based on gender, income and profession. Based on the result from correspondent, there is a little bit significant difference for the gender group. Furthermore, there are significant differences for the age and profession group based on the questionnaire that has been given.